STRATEGI PEMBINAAN REMAJA BERBASIS PENDIDIKAN ISLAM DALAM MENINGKATKAN KESADARAN BERAGAMA KELURAHAN TALAGA 1 KABUPATEN BUTON TENGAH - Aisa Arif; Basri; La Jusu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article examines youth coaching strategies in improving religious awareness in Talaga 1 Village, Central Buton Regency. Youth development is understood as an effort to internalize Islamic educational values into social life through structured religious activities. This study aims to analyze the condition of adolescents’ religious awareness, the coaching strategies implemented, as well as the supporting and inhibiting factors. This research employs a field research method with a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and were analyzed using content analysis techniques. The findings indicate that the coaching strategies include habituation of congregational prayers, regular religious studies, exemplary leadership of religious figures, mosque youth organization activities, and persuasive and dialogical approaches. These strategies contain values of faith (aqidah), worship (ibadah), morality (akhlaq), and social responsibility that contribute to shaping adolescents’ religious character. The study concludes that planned and contextual coaching is effective as a form of non-formal Islamic education in strengthening youth religious awareness in rural communities.